Malnutrition in pre-school children (2-5 years of age) in district Swabi(NWFP)-Pakistan - Khattak, Muhammad Muzaffar Ali Khan (2007)
Infancy and preschool age is an important stage of life where the nutrition plays an important role and long lasting effects in the later years of life. This study was conducted in the two Tehsils namely Lahore and Swabi of the District Swabi, North West Frontier Province (NWFP)-Pakistan. The aim of the study was to identify the extent of malnutrition in the preschool children with age range of 24 -60 months, in this particular area. A representative sample of 140 children (70 from each Tehsil) both boys and girls were randomly selected for the study. The age, sex, anthropometric measurements (height and weight only), family size and other socio-economic factors were recorded in the preplanned questionnaire. The data was compiled and fed to the Epi Info software and analyzed as desired for the various parameters. The mean ± SD for heights and weights were calculated and compared with the recommended growth chart for Pakistan. Furthermore, Z-score for age-height & weight, sex-height & weight, height-weight and Z- score for BMI were determined. The association of the family size and other socio-economic factors was also evaluated using the scored correlation analysis. The results showed no significant differences between the sex, age for weight and height compared in the whole district or in the two Tehsil. The weight and height were lower than the third percentile in all cases and indicate that t he children are stunted and under-weight. The mean z-score in every case (i.e.-score for age-height & weight, sex-height & weight, height-weight and Z- score for BMI) was significantly (P<0.001) different. Furthermore, there was significant association with family size and income of the parents with the children nutritional status. This study indicates that the children in this particular area on average are at the risk of malnutrition.